1990
DOI: 10.1111/j.1365-2648.1990.tb01859.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cerumen removal on the hearing ability of geriatric patients

Abstract: The purposes of this study were to estimate the prevalence of impacted cerumen in a population of hospitalized elderly patients, and to evaluate the effect of cerumen removal in reversing hearing impairment. The design was a pre-test/post-test static-group comparison. Over a 1-year period, a random sample (n = 226) was drawn every third day from daily admission lists of English-speaking patients aged 65 or older, admitted to non-intensive care units of one hospital. On either the second or third day of hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 13 publications
3
44
2
Order By: Relevance
“…This frequency was quite low compared with Western countries. [2][3][4]10 The prevalence of wet type cerumen in the present study was 25.5%, and the incidence of wet cerumen with impaction and wet cerumen without impaction was not significantly different. The cause of a non-significant incidence of wet cerumen impaction in the present study might be due to the low participants.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This frequency was quite low compared with Western countries. [2][3][4]10 The prevalence of wet type cerumen in the present study was 25.5%, and the incidence of wet cerumen with impaction and wet cerumen without impaction was not significantly different. The cause of a non-significant incidence of wet cerumen impaction in the present study might be due to the low participants.…”
Section: Discussionmentioning
confidence: 73%
“…[2][3][4][5][6] Moore et al reported that 65.6% of residents in a skilled nursing facility had cerumen impaction in at least one ear. 10 The reason for a higher prevalence of cerumen impaction in people with an intellectual disability is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,18 In the developmentally delayed adult population, 28% to 36% have excessive or impacted cerumen. 10,11 Moreover, the presence of cerumen impaction has been associated with hearing loss 19 and diminished cognitive function 15 in these populations. The prevalence of cerumen impaction varies widely but is still high in healthy adults and children.…”
Section: Health Care Burdenmentioning
confidence: 99%
“…15 Removing impacted cerumen can improve hearing. 9,15,19,60 If the patient has relevant symptoms (pain, tinnitus, hearing loss, aural fullness, or vertigo) and the ear is impacted with cerumen, cerumen impaction may be a contributing factor for the symptoms.…”
Section: Supporting Textmentioning
confidence: 99%